Cryptic haplotypes of "Candidatus Liberibacter africanus" - (:unkn) unknown (My University, 2015)
“Candidatus Liberibacter africanus” (Laf) has long been recognised as a causal agent of the devastating citrus disease huanglongbing (HLB) or citrus greening. This species is currently restricted to Africa, the Arabian Peninsula and some Indian Ocean islands and vectored by the African citrus psyllid, Trioza erytreae. Blotchy mottle on citrus leaves is characteristic of the disease. Somewhat similar symptoms in the Rutaceous tree Calodendrum capensis (Cape Chestnut) resulted in the discovery of Laf outside commercial citrus crops in South Africa. This was classed as a subspecies of Laf (capensis, hence LafC). In subsequent surveys of both commercial citrus crops and Calodendrum, both natural and ornamental specimens, LafC was not found in the citrus crop, nor has Laf been found in C. capensis. HLB was reported from Madagascar in 1968 but no sequences from this source have so far been published. Until fairly recently, only the reference 16S rRNA gene sequences of Laf (L22533) and LafC (AF137368) had been deposited in GenBank. Both of these reference sequences contain a number of unresolved nucleotides. Resolving these nucleotide positions by aligning against more recently available sequences, it becomes evident that these unresolved positions represent one percentage point difference in similarity between Laf and LafC. The originally reported 97.4% similarity is therefore incorrect based on this new information. Recalculating the similarity on the full length 16S rDNA sequence results in 99.54% similarity, a value too high to justify a subspecies status. LafC should therefore be reduced to that of a haplotype of Laf. Further, the six 16S rRNA gene sequences currently available in GenBank identified as the species Laf separate into 2 haplotype groups. The 3 haplotypes of Laf are therefore LafA designated as the first accession sequenced (L22533), LafC for the former capensis subspecies and to recognise the prior use of this term, and LafB for the thi
Keywords: African Research